2021
DOI: 10.3390/cells10123471
|View full text |Cite
|
Sign up to set email alerts
|

GLIS3: A Critical Transcription Factor in Islet β-Cell Generation

Abstract: Understanding of pancreatic islet biology has greatly increased over the past few decades based in part on an increased understanding of the transcription factors that guide this process. One such transcription factor that has been increasingly tied to both β-cell development and the development of diabetes in humans is GLIS3. Genetic deletion of GLIS3 in mice and humans induces neonatal diabetes, while single nucleotide polymorphisms (SNPs) in GLIS3 have been associated with both Type 1 and Type 2 diabetes. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 99 publications
0
7
0
Order By: Relevance
“…GLIS3 has been shown to directly regulate the transcription of targeted genes in β cells, including Ins2 , Ngn3, and Ccnd2 . 36 , 39 Of note, we found that the expression levels of Ins2 , Ngn3, and Ccnd2 were reduced by overexpressing circGlis3 in MIN6 cells and islets ( Figure S6 G and S6H). Given that Glis3-348aa bound to the C-terminal TAD of GLIS3 protein, we then wondered whether the transcriptional activity of GLIS3 was affected by Glis3-348aa.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…GLIS3 has been shown to directly regulate the transcription of targeted genes in β cells, including Ins2 , Ngn3, and Ccnd2 . 36 , 39 Of note, we found that the expression levels of Ins2 , Ngn3, and Ccnd2 were reduced by overexpressing circGlis3 in MIN6 cells and islets ( Figure S6 G and S6H). Given that Glis3-348aa bound to the C-terminal TAD of GLIS3 protein, we then wondered whether the transcriptional activity of GLIS3 was affected by Glis3-348aa.…”
Section: Resultsmentioning
confidence: 82%
“…GLIS3 protein, which is encoded by the Glis3 gene, is a transcription factor responsible for β-cell differentiation and insulin secretion. 36 The colocalization of Glis3-348aa and GLIS3 was observed in the nucleus of MIN6 cells ( Figure 6 A), and thus we wondered whether there was an interaction between Glis3-348aa and GLIS3 protein. Co-IP assays with anti-Glis3-348aa antibody showed that Glis3-348aa could interact with GLIS3 protein in MIN6 cells and mouse islets ( Figures 6 B and S6 B).…”
Section: Resultsmentioning
confidence: 96%
“…Gli-similar 3 (Glis3), a transcription factor, is critical in b-cell development and proliferation, as well as the regulation of insulin gene expression [ 96 , 97 ]. Several single-nucleotide polymorphisms (SNPs) in Glis3 have been closely associated with T2D [ 98 ].…”
Section: Ptms In Type 2 Diabetesmentioning
confidence: 99%
“…The genetic pathways involved in different stages of the disease are highly divergent, and genetics is currently the only tool capable of detecting those at risk before the development of islet autoimmunity [75]. More and more genetic-based evidence points to the predisposition at the β-cell level, with risk variants affecting the susceptibility to pro-apoptotic stimuli and influencing β-cell phenotypes [50,57,76]. New in-depth analyses of the potential role of genetic variants in the progression from islet autoimmunity to clinical T1D at the genome-wide level using next-generation sequencing identified several novel risk genes associated with T1D.…”
Section: Regulating the Effects Of Cytokines Inside β-Cells For Proap...mentioning
confidence: 99%